The effects of a multistep intercooled compression process implemented on a solar-driven Braysson heat engine. (1st January 2015) - Georgiou, D.P.; Milidonis, K.F.; Georgiou, E.N.
Highlights: Thermodynamic analysis of a solar driven power plant running on the Braysson cycle. Isothermal compression is implemented by the use of multistage intercooled compression stages. The plant's thermal efficiency is investigated and compared against other cycles. Abstract: The present study develops the thermodynamic analysis for the cycle of a solar-driven, Braysson cycle based plant in the ideal limit and in the presence of process irreversibilities. The plant cycle differs from the conventional idealized Braysson cycle in that the implementation of the final isothermal compression process is substituted by a multistep intercooled compression. The cycle's efficiency is analytically formulated after taking into account several loss (irreversibility) sources such as the non-isentropic behavior of the main compressor, the power turbine and the intercooled compressor stages as well as the actual heat transferred through countercurrent heat exchangers. All pressure losses associated with heat exchangers are related to the actual heat transfer load within each exchanger. The analysis develops a parametric evaluation for the effectiveness of the main cycle free variables on the thermal efficiency of the cycle. Such free variables include the working fluid maximum temperature, the compressor pressure ratio and the operating temperature limits of the intercooled compression stages, in addition to the polytropic coefficients of the compressor and power turbine (quasi-) isentropic processes. The results indicate that such a plant may reach efficiency levels above 30%, i.e. exceeding the efficiencies of the conventional Photovoltaic plants by a wide margin.